The effects of performance appraisal on employee retention. A comparison of Finnish and Vietnamese enterprises - Nguyen, Ha Thu (My University, 2015)
Purpose: This research aims to identify the features of a performance appraisal system and explore how each feature affects the employees’ loyalty. Furthermore, the study would like to discover if these effects are different in different cultures. Methodology: Applying qualitative method, data was collected through 15 semi-structured interviews (7 cases were conducted in Finland and 8 cases were interviewed in Vietnam). Participants chosen for the research are knowledge employees working in Vietnamese or Finnish original enterprises. Findings: Four features of a performance appraisal system, which are goals setting, supervisor – subordinate relationship, rewards linked with performance result and fairness issue are argued based on literature review. From empirical studies, variety of findings is identified supporting and supplementing for existing theories. One of those is the emphasis of self-development based performance appraisal in Finland and the rewarding based one in Vietnam. The performance appraisal system has weak impact on Finnish employees’ loyalty; while it does influence Vietnamese individual intention to leave the job. The findings also illustrate that Finnish staff take clear goals setting and fairness as prerequisite features of a performance appraisal; Vietnamese employees, in contrast, view the relationship with supervisor and rewards received as more significant criteria. Practical implications: This study provides suggestions of retaining talents for managerial practices. Findings of the research could assist international managers to concentrate on features which strongly affecting the employees’ satisfaction and loyalty when they design and implement performance appraisal system in different locations.
Keywords: Performance appraisal; Employee retention; Fairness issue; Goals setting; Relationship with supervisor; Rewards; Cultural differences; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|